Osobowość ekologiczna płci - badania ankietowe - Irena Grochowska (Studia Ecologiae et Bioethicae)
After analysing the above answers we can deduct some results, which confirm certain behaviour in girls that can be scientifically explained. A survey helped in establishing ecological consciousness and was a help in characterizing a survival persona. Looking at the answers with inclusion of two different sexes we can follow differences in the views concerning environmental protection, the survey results clearly show a difference in approach to the natural environment depending on the sex. Women more clearly see the beauty, harmony and set order in the environment. Nature astonishes them and is a guarantee of life. Analysing the survey results it is not possible not to see the differences in viewing the natural environment. Quoting Estes we can say that mature woman (surviving woman) looking at a forest sees a home for herself and other people, whilst others looking at the same forest imagine cutting down trees and making money on it.